2011
DOI: 10.1007/s10646-011-0626-0
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based metabolic profiling for serum of mouse exposed to source water

Abstract: (1)H nuclear magnetic resonance (NMR) based metabonomic method was used to characterize the profile of low-molecular-weight endogenous metabolites in mouse (Mus musculus) serum following exposure to Taihu Lake source water for 90 days. The (1)H NMR spectra of mice sera were recoded and a total of 21 metabolites were identified. Data reduction and latent biomarkers identification were processed by pattern recognition (PR) analysis. The principal component analysis (PCA) and partial least square discriminant ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…During the same exposure period of this study, another 20 mice were fed with pure water and Lake Taihu water under the same conditions. 1 H nuclear magnetic resonance (NMR) based metabonomic method was used to characterize the profiles of low‐molecular‐weight endogenous metabolites in mouse serum (Zhang et al ., ). The results showed that the raw lake water perturbed the energy and amino acid metabolism, which was partly consistent with the results of serum biochemistry analysis and microarray analysis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…During the same exposure period of this study, another 20 mice were fed with pure water and Lake Taihu water under the same conditions. 1 H nuclear magnetic resonance (NMR) based metabonomic method was used to characterize the profiles of low‐molecular‐weight endogenous metabolites in mouse serum (Zhang et al ., ). The results showed that the raw lake water perturbed the energy and amino acid metabolism, which was partly consistent with the results of serum biochemistry analysis and microarray analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Before exposure of the mice, 22 organic pollutants and 20 trace elements in water samples were determined. The monitoring data have been discussed in our previous report (Zhang et al ., ). In order to identify in detail the potential health effects of the measured pollutants, in this study, human health risk assessment was carried out.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation